2016
DOI: 10.4149/304_150806n433
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cisplatin resistance by inhibiting PI3K/Akt signal pathway in human lung cancer cells

Abstract: Cisplatin is regularly used in the treatment of lung cancer. However, its efficacy is limited because of drug resistance. In this study, we found that Akt expression and activity was increased in lung cancer cells with acquired cisplatin resistance (A549/DDP cells and H460/DDP cells) when compared to their parental cells. Inhibition of phosphatidylinositol 3-kinase (PI3K)/Akt kinase activity by its natural inhibitor, Wortmannin, could sensitize DDP-resistant cells to DDP and reverse DDP resistance. Combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…Consistent with recent studies associating loss of PER2 with chemoresistance in cancer [17,26,27], we found that SKOV3/DDP cells had dramatically decreased mRNA levels of PER2 compared with parental cells. Previous studies have shown that microRNAs, such as miR-24, miR-449a, and miR-484, inhibit PER2 transcription by binding to its 3'-untranslated region [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with recent studies associating loss of PER2 with chemoresistance in cancer [17,26,27], we found that SKOV3/DDP cells had dramatically decreased mRNA levels of PER2 compared with parental cells. Previous studies have shown that microRNAs, such as miR-24, miR-449a, and miR-484, inhibit PER2 transcription by binding to its 3'-untranslated region [28,29].…”
Section: Discussionsupporting
confidence: 92%
“… 25 Furthermore, activated AKT plays an important role in cisplatin resistance of lung cancer. 26 , 27 Thus, our results lead to the following hypothesis: S100A16 induces the metastatic potential and resistance to platinum-based adjuvant chemotherapy of lung adenocarcinoma through the activation of the AKT signaling pathway. EMT is a process whereby epithelial cells lose polarity and cell–cell adhesion and progress to invasive mesenchymal cells.…”
Section: Discussionmentioning
confidence: 59%
“…Currently, it is generally believed that PTEN, as the main inhibitor of the PI3K/AKT signaling pathway, can negatively regulate the signaling pathway by dephosphorylating PIP3 to generate PIP2, which results in the downregulation of p-AKT, thus inhibiting the proliferation of cancer cells ( Tay et al, 2011 ; Russell et al, 2018 ). Interestingly, Zhang et al reported that Wortmannin sensitized DDP-resistant human lung cancer cells by downregulating the PI3K/AKT signaling pathway ( Zhang et al, 2016 ), which prompted us to question whether hesperetin could also enhance the sensitivity of GC cells to DDP by inhibiting this pathway. Furthermore, a recent study showed that hesperetin inhibited the PI3K/AKT signaling pathway by upregulating PTEN expression, thus inhibiting cell proliferation ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%